Healthcare-associated infections in pediatric cancer patients: results of a prospective surveillance study from university hospitals in Germany and Switzerland - Rutkowski Stefan; Schlegel Paul-Gerhardt; Gravou Chara; Schwamborn Dorothee; Wenchel Hans-Martin; Fleischhack Gudrun; Bode Udo; Ammann Roland A; Simon Arne; Dannenberg Claudia; Körholz Dieter; Laws Hans; et al. (BMC Infectious Diseases, 2008)
Abstract Background Pediatric cancer patients face an increased risk of healthcare-associated infection (HAI). To date, no prospective multicenter studies have been published on this topic. Methods Prospective multicenter surveillance for HAI and nosocomial fever of unknown origin (nFUO) with specific case definitions and standardized surveillance methods. Results 7 pediatric oncology centers (university facilities) participated from April 01, 2001 to August 31, 2005. During 54,824 days of inpatient surveillance, 727 HAIs and nFUOs were registered in 411 patients. Of these, 263 (36%) were HAIs in 181 patients, for an incidence density (ID) (number of events per 1,000 inpatient days) of 4.8 (95% CI 4.2 to 5.4; range 2.4 to 11.7; P < 0.001), and 464 (64%) were nFUO in 230 patients. Neutropenia at diagnosis correlated significantly with clinical severity of HAI. Of the 263 HAIs, 153 (58%) were bloodstream infections (BSI). Of the 138 laboratory-confirmed BSIs, 123 (89%) were associated with use of a long-term central venous catheter (CVAD), resulting in an overall ID of 2.8 per 1,000 utilization days (95% CI 2.3 to 3.3). The ID was significantly lower in Port-type than in Hickman-type CVADs. The death of 8 children was related to HAI, including six cases of aspergillosis. The attributable mortality was 3.0% without a significant association to neutropenia at time of NI diagnosis. Conclusion Our study confirmed that pediatric cancer patients are at an increased risk for specific HAIs. The prospective surveillance of HAI and comparison with cumulative multicenter results are indispensable for targeted prevention of these adverse events of anticancer treatment.